The influence of culture into architectural facade for cultural and art centre in Kelantan - Aziz, Nurul Syaheera; Mohd Siraj, Suhailah M; Ismail, Alice Sabrina; Rahmat, Muhamad Hanafi (Universiti Teknologi MARA, Perak, 2025)
This study focuses on how culture affects a proposed cultural and arts center in Kelantan, and its architectural facade. This research aims to identify specific cultural elements that impact local design, focusing on traditional architectural forms, materials, and motifs. It provides a comprehensive understanding of how local culture influences a building's appearance and functionality by documenting these effects. The research went on to examine the benefits of applying culturally informed design in tropical climates, emphasising improvements in ventilation, thermal comfort, and weather protection. In the end, this research uses this understanding to ensure that the facade of the Culture and Art Centre embraces Kelantan's cultural legacy while also fulfilling functional requirements. The results seek to further the conversation on culturally responsive architecture by providing a template for incorporating traditional components into modern buildings while maintaining and promoting regional identity. Other than that, a lot lack awareness of or value the significance of protecting Kelantan's architectural legacy. The younger generation may be unaware of how crucial traditional facades are to the region's history, culture, and identity.